The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21608/eajbsf.2020.113976
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of Combined Administration of Vitamins C and Curcumin on Cypermethrin - Induced Oxidative Stress in Male Albino Rats.

Abstract: Back Ground: Cypermethrin (CPM) is non-systematic type II synthetic pyrethroid, commonly used for pest control in livestock, forestry, horticulture, household, public and animal health services, private homes, and animal husbandry. By scavenging free radicals and modulating antioxidant protection mechanism, plant phytochemicals (vitamin C and Curcumin) are known to exert their protective impact, Aim: The current research aimed to examine the ameliorative effect of combining curcumin with prevention of vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The decrease in CAT activity might be due to the utilization of enzymes in overcoming the effect of oxidative stress (Ince et al 2012). Our study aligns with the other studies, Ziada et al (2020) showed that oral supplementation of 200 mg/kg/b.w. CYP for 28 days brings about oxidative stress in the serum and brain, as indicated by reduced CAT activity.…”
Section: Discussionsupporting
confidence: 91%
“…The decrease in CAT activity might be due to the utilization of enzymes in overcoming the effect of oxidative stress (Ince et al 2012). Our study aligns with the other studies, Ziada et al (2020) showed that oral supplementation of 200 mg/kg/b.w. CYP for 28 days brings about oxidative stress in the serum and brain, as indicated by reduced CAT activity.…”
Section: Discussionsupporting
confidence: 91%
“…CPM leads to a significant increase in MDA and protein carbonyl (PC) levels in serum, the liver, and the brain, while antioxidant biomarkers are significantly reduced in serum and brain tissues. Ziada et al [ 35 ] indicated that plant phytochemicals such as vitamin C and curcumin play a protective role against cypermethrin-induced oxidative stress in serum, the brain, and the liver. Curcumin, in addition to its antioxidative and free-radical-scavenging abilities, also enhances the activity of other antioxidants [ 35 ].…”
Section: Curcumin In Stress Management Of Terrestrial Animalsmentioning
confidence: 99%
“…Ziada et al [ 35 ] indicated that plant phytochemicals such as vitamin C and curcumin play a protective role against cypermethrin-induced oxidative stress in serum, the brain, and the liver. Curcumin, in addition to its antioxidative and free-radical-scavenging abilities, also enhances the activity of other antioxidants [ 35 ]. Heavy metals such as cadmium (Cd) can cause damage to various organ systems in animals after long-term exposure.…”
Section: Curcumin In Stress Management Of Terrestrial Animalsmentioning
confidence: 99%